2019
DOI: 10.3390/cancers11121840
|View full text |Cite
|
Sign up to set email alerts
|

ANLN and TLE2 in Muscle Invasive Bladder Cancer: A Functional and Clinical Evaluation Based on In Silico and In Vitro Data

Abstract: Anilin actin binding protein (ANLN) and transducing-like enhancer protein 2 (TLE2) are associated with cancer patient survival and progression. The impact of their gene expression on progression-free survival (PFS) of patients with muscle invasive bladder cancer (MIBC) treated with radical cystectomy (RC) and subtype association has not yet been investigated. qRT-PCR was used to measure the transcript levels of ANLN and TLE2 in the Mannheim cohort, and validated in silico by The Cancer Genome Atlas (TCGA) coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…Expression of vimentin was found in 69% cases of transitional cell carcinoma and its expression is associated with the grade of transitional cell carcinoma [ 41 ]. In accordance with our study, Wu et al have also identified the expression of Anilin actin binding protein to be subtype-specific [ 42 ]. Similarly, the expression of Anilin actin binding protein was higher in the basal subtype compared to luminal subtype in bladder cancer cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Expression of vimentin was found in 69% cases of transitional cell carcinoma and its expression is associated with the grade of transitional cell carcinoma [ 41 ]. In accordance with our study, Wu et al have also identified the expression of Anilin actin binding protein to be subtype-specific [ 42 ]. Similarly, the expression of Anilin actin binding protein was higher in the basal subtype compared to luminal subtype in bladder cancer cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Transcriptome sequencing identified ANLN as a potential prognostic biomarker in bladder urothelial carcinoma [118]. Based on in silico and in vitro data, ANLN and TLE2 are shown to be potential biomarkers for muscle invasive bladder cancer [168]. ANLN was found as a target of head and neck squamous cell carcinomas via genome-wide gene expression profiling [169].…”
Section: Anln As a Biomarkermentioning
confidence: 99%
“…High TLE2 expression was associated with favorable OS. The TCGA cohort confirmed that low TLE2 expression was associated with shorter OS and DFS [36].…”
Section: Tle1 Is Aberrantly Expressed or Upregulated In Various Typesmentioning
confidence: 63%